Probiotic Lacticaseibacillus rhamnosus GR-1 and Limosilactobacillus reuteri RC-14 as an Adjunctive Treatment for Bacterial Vaginosis Do Not Increase the Cure Rate in a Chinese Cohort: A Prospective, Parallel‐Group, Randomized, Controlled Study - Zhang, Yongke; Lyu, Jinli; Ge, Lan; Huang, Liting; Peng, Zhuobing; Liang, Yiheng; Zhang, Xiaowei; Fan, Shangrong (Frontiers in Cellular and Infection Microbiology, 2021)
The purpose of this study was to evaluate the effectiveness of metronidazole and oral probiotics adjunct to metronidazole in the treatment of bacterial vaginosis (BV). One hundred and twenty-six Chinese women with BV were enrolled in this parallel, controlled trial, and were randomly assigned into two study arms: the metronidazole group, which was prescribed metronidazole vaginal suppositories for 7 days, and the adjunctive probiotic group, which received Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 orally for 30 days as an adjunct to metronidazole. Clinical symptoms and Nugent scores at the initial visit, 30 days and 90 days were compared. There was no significant difference of the 30-day cure rate between the adjunctive probiotic group (57.69%) and the metronidazole group (59.57%), with an odds ratio (OR) of 0.97 (95% confidence interval (CI), 0.70 to 1.35, p-value = 0.04), or of the 90-day cure rate (36.54% vs 48.94%, OR, 0.75; 95% CI, 0.47 to 1.19; p-value = 1.55). Also, no significant difference of the vaginal and faecal microbial diversity and structure between the two groups at 0, 30 or 90 days were shown based on 16S rRNA sequences. The probiotic species were rarely detected in either the vaginal microbiota or the faecal microbiota after administration which may revealed the cause of noneffective of oral probiotics. No serious adverse effects were reported in the trial. The study indicated that oral probiotic adjunctive treatment did not increase the cure rate of Chinese BV patients compared to metronidazole.